Analisis Waktu dan Biaya Menggunakan Metode Time Cost Trade Off Rehabilitasi Gedung Kantor Inspektorat Daerah Kabupaten Tuban - Susilo Susilo; Hammam Rofiqi Agustapraja; Samsul Arif (Universitas Batanghari Jambi, 2026)
Delays in construction projects often lead to cost increases, reduced quality, and even the risk of penalties. This was the case in the Rehabilitation Project of the Regional Inspectorate Office Building of Tuban Regency, which experienced a 4.735% progress deviation in the 14th week. Such delays could affect the overall completion and increase project costs. This research aims to analyze the relationship between project time and cost using the Time Cost Trade Off method to find an efficient way to speed up the project. The study was carried out by collecting field data, analyzing the S-curve, identifying the critical path with the Critical Path Method , and simulating different overtime scenarios. From the three overtime options tested, adding 3 extra hours per day turned out to be the most effective choice. This scenario successfully shortened the project duration and achieved a 0.207% cost efficiency without causing significant changes to the work structure. This means that the application of the Time Cost Trade Off method is effective in optimizing resources, reducing the negative impact of delays, and maintaining a balance between time and cost in similar construction projects